265 Effects of non-Starch Polysaccharide Degrading Enzymes + Lysophospholipids in Feeds with Varied ME Contents on Growth Performance and Nutrient Utilization of Pigs from 25 to 75 Kg BW. (21st September 2022) - Baker, Jonathan; Kim, Sung Woo
Abstract: This study aimed to investigate efficacy of the combinational use of non-starch polysaccharide degrading enzymes (NSPase) and lysophospholipids (LPL) on growth performance and nutrient utilization in pigs fed feeds with varied metabolizable energy (ME) levels. Grower pigs (n = 270; 28.1 ± 0.6 kg BW) were allotted in a randomized complete block design with a 3 x 3 factorial arrangement of treatments fed for 51 d in 2 phases (30 and 21 d, respectively). Two factors were ME (3, 260, 3, 335, and 3, 410 kcal/kg) and NSPase + LPL (ELPL at 0.00, 0.05, and 0.10%). Growth performance and backfat were measured. Blood was collected to measure plasma urea nitrogen (PUN) concentrations. Data were analyzed using the MIXED procedure on SAS 9.4. Increasing ME tended to increase (P = 0.066) ADG during Grower 2 and increased (P < 0.05) G/F during the overall period. Increasing ELPL supplementation increased (P < 0.05) both ADG and ADFI during Grower 2, whereas it tended to reduce (P = 0.084) G/F during the overall period. Supplemental effects of ELPL on increasing ADG was prominent (P < 0.05) at high ME content (3% above NRC requirement). Supplementation of ELPL tended to reduce (P = 0. 057) G/F during Grower 2 at low ME content (3% below NRC requirements). Backfat thickness and NEFA were not influenced by 2 factors. Increasing ME increased (P < 0.05) PUN during Grower 1 whereas increasing ELPL tended to increase (P = 0.077) PUN during Grower 2. In conclusion, supplementation of ELPL enhanced growth and feed intake of pigs from 50 to 75 kg BW, especially when dietary ME was above NRC requirement (3%) by fat supplementation (4%). These improvements may be due to increased nutrient utilization as indirectly indicated by increased PUN during fed status.